RASIONALISME, EMPIRISME DAN KONTRUKTIVISME DALAM PENDIDIKAN DI SMP NEGERI 51 MERANGIN - HASMAILENA SARAGIH; KEN HAWARI; DESI KHORIDATUL (STKIP Subang, 2026)
This article discusses three major educational philosophies, namely rationalism, empiricism, and constructivism, and their relevance to the learning process at SMPN 51 Merangin. The purpose of this study is to analyze the role of these three philosophical approaches in supporting effective, meaningful, and student-centered learning in the modern educational era. The research employed a qualitative approach using a library research method by collecting data from various sources, including books, scientific journals, and relevant educational documents. Data were analyzed using content analysis techniques, including data reduction, data presentation, and conclusion drawing. The findings indicate that rationalism plays an important role in developing students' logical and systematic thinking skills, empiricism provides direct learning experiences through observation and experimentation, while constructivism emphasizes students' active involvement in constructing their own knowledge through social interaction and reflection. These three approaches complement one another in improving the quality of learning at SMPN 51 Merangin. However, their implementation still faces several challenges, such as limited facilities, differences in students' abilities, and learning habits that remain relatively passive. Therefore, the integration of these three educational philosophies is essential to create active, creative, and meaningful learning experiences.